2017
DOI: 10.1002/nau.23369
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamics in patients with spinal cord injury: A clinical review and best practice paper by a working group of The International Continence Society Urodynamics Committee

Abstract: Urodynamic is highly recommended for patients with SCI after a proper initial assessment. Regular urodynamic follow-up is recommended to avoid upper urinary tract damage. However, until now, there is limited evidence on how frequently urodynamic control should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Some studies suggested that urodynamic examination should be performed after the recovery of bladder function following acute SCI, three months after injury (13). The members of the International Continence Society (ICS) Urodynamics Committee on the SCI core panel recommend performing the first exam as soon as possible after the end of the spinal shock phase and then conducting repeated testing at 6 and 12 months after the injury (21).…”
Section: Implications For Practicementioning
confidence: 99%
“…Some studies suggested that urodynamic examination should be performed after the recovery of bladder function following acute SCI, three months after injury (13). The members of the International Continence Society (ICS) Urodynamics Committee on the SCI core panel recommend performing the first exam as soon as possible after the end of the spinal shock phase and then conducting repeated testing at 6 and 12 months after the injury (21).…”
Section: Implications For Practicementioning
confidence: 99%
“…Timely establishment of urodynamic observations during the initial period post-injury and continued life-long monitoring of detrusor overactivity is paramount after SCI [23], given the negative effects of NDO on the upper urinary tracts and the association with increased frequency and severity of UTIs. We propose yearly investigations until a stable urodynamic situation and stable bladder management have been reached.…”
Section: Discussionmentioning
confidence: 99%
“…The ICS recommended annual urological monitoring, to detect complications and to adjust bladder management [ 22 ]. More specifically, Schurch et al and the GENULF recommended in patients with dysraphism or spinal cord injury a yearly examination because of their “high-risk” bladder, which could be delayed by one to two years after attaining controlled NLUTD [ 2 , 3 ]. De Sèze et al recommended a cystometry every one to three years in MS patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%